PENGARUH KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KOTA SERANG - Gentari, Ratu Erlina (Universitas Serang Raya, 2015)
This study aims to determine the effect of leadership, organizational climate and the performance of employees at Dinas Pekerjaan Umum Kota Serang. The sample in thisstudy as many as 34 respondents taken entirely out of the total population of employees at Dinas Pekerjaan Umum Kota Serang as many as 34 people. The analysis method used in this research is multiple linear regression analysis method to perform testing of the F-test, t-test and classical assumption. Analysis Tools using SPSS software Version 19.The research proves that the leadership and organizational climate positive and significant impact on the performance of employees at Dinas Pekerjaan Umum Kota Serang.